LOV (light, oxygen, or voltage) domains of the blue-light photoreceptor phototropin (nph1): Binding sites for the chromophore flavin mononucleotide - Christie, John M. (The National Academy of Sciences, 1999)
Phototropism, the bending response of plant organs to or away from a directional light source, is one of the best studied blue light responses in plants. Although phototropism has been studied for more than a century, recent advances have improved our understanding of the underlying signaling mechanisms involved. The NPH1 gene of Arabidopsis thaliana encodes a blue light-dependent autophosphorylating protein kinase with the properties of a photoreceptor for phototropism. NPH1 apoprotein noncovalently binds FMN to form the holoprotein nph1. The N-terminal region of the protein contains two LOV (light, oxygen, or voltage) domains that share homology with sensor proteins from a diverse group of organisms. These include the bacterial proteins NIFL and AER, both of which bind FAD, and the phy3 photoreceptor from Adiantium capillus-veneris. The LOV domain has therefore been proposed to reflect a flavin-binding site, regulating nph1 kinase activity in response to blue light-induced redox changes. Herein we demonstrate that the LOV domains of two nph1 proteins and phy3 bind stoichiometric amounts of FMN when expressed in Escherichia coli. The spectral properties of the chromopeptides are similar to the action spectrum for phototropism, implying that the LOV domain binds FMN to function as a light sensor. Thus, our findings support the earlier model that nph1 is a dual-chromophoric flavoprotein photoreceptor regulating phototropic responses in higher plants. We therefore propose the name phototropin to designate the nph1 holoprotein.